An Implicit Algorithm of Solving Nonlinear Filtering Problems (Communications in Computational Physics, 2014)
Nonlinear filter problems arise in many applications such as communications and signal processing. Commonly used numerical simulation methods includeKalman filter method, particle filter method, etc. In this paper a novel numerical algorithm is constructed based on samples of the current state obtained by solving thestate equation implicitly. Numerical experiments demonstrate that our algorithm ismore accurate than the Kalman filter and more stable than the particle filter.